Analysis of flood control risk in floodwater utilization considering the uncertainty of flood volume and peak - Du, Huihua; Wang, Zongzhi; Yin, Jun (Frontiers in Earth Science, 2023)
A design flood is a hypothetical flood used for the design of reservoirs and other hydrologic engineering infrastructures. Among many hydrological properties of a design flood, flood volume and peak can significantly affect the safety of reservoir operation. However, the uncertainty of flood volume and peak has rarely been considered in the risk analysis of reservoir operation regarding floodwater utilization. In this paper, a general risk analysis framework that integrates the Monte Carlo sampling method and the most likely event selection method is proposed to calculate the risk of operating a single reservoir. By generating a large amount of stochastic bivariate flood data, the most likely design values were selected for a given return period. The probability of the maximum water level exceeding the current design flood level was calculated based on the simulation of flood control operation under various floodwater utilization schemes. The model is applied to the Shagou reservoir in the Shuhe River basin, China. The results show that the design flood volume and flood peak obtained by the bivariate joint return are 7.59% and 8.22% higher than those from univariate frequency analysis, respectively; the joint return period of bivariate design value spans from 10a to 1000a compared to the historical data; and the flood control risk at Shagou reservoir is 0.29 under current flood control operations based on the uncertainty of flood volume and peak. Moreover, the marginal benefit may contain floodwater utilization and a transmission risk effect between different node projects in the flood control system.